Effect of Pre-Hydrolysis by Alcalase on Enzymatic Membrane Reactor Performance in Production of Low Molecular Weight Peptide from Nile Tilapia Skin Gelatin - Tauntong, Mantaka; Sirinupong, Nualpun; Youravong, Wirote (Agriculture and Natural Resources, 2014)
Enzymatic hydrolysis, performed under batch processing has several disadvantages including low productivity. To overcome some limitations, an enzymatic membrane reactor (EMR) has been proposed. Pre-hydrolysis possibly plays an important role in EMR performance. Therefore, the effects of pre-hydrolysis were investigated in an enzymatic reactor on the membrane performance of a low molecular weight peptide produced from Nile tilapia skin gelatin containing 4 % weight per weight alcalase at 50 °C, pH 8.0. The gelatin solution was pre-hydrolyzed for 0, 15, 30 or 60 min before passing through the 1 kDa molecular weight cutoff ultrafiltration membrane. The permeate flux, protein conversion, capacity, productivity, fouling resistance and angiotensin-I converting enzyme inhibitory activity were investigated. The results showed that the pre-hydrolysis time had a significant effect on the gelatin solution viscosity permeate flux and fouling. The results also indicated that pre-hydrolysis could noticeably increase EMR performance. A pre-hydrolysis gelatin solution pre-hydrolyzed with alcalase for 60 min was required to enhance the EMR performance during the production of low molecular weight peptides from Nile tilapia skim gelatin.